2007
DOI: 10.1017/s1355617707071032
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in adolescent marijuana users: Subtle deficits detectable after a month of abstinence

Abstract: In adults, studies examining the long-lasting cognitive effects of marijuana use demonstrate subtle deficits in attention, executive function, and memory. Because neuromaturation continues through adolescence, these results cannot necessarily generalize to adolescent marijuana users. The goal of this study was to examine neuropsychological functioning in abstinent marijuana using and demographically similar control adolescents. Data were collected from 65 adolescent marijuana users (n 5 31, 26% females) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
264
5
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(300 citation statements)
references
References 102 publications
(115 reference statements)
25
264
5
6
Order By: Relevance
“…In addition, the activation of the brain cannabinoid system causes deficits in attention, executive functioning, and short-term memory (Lichtman and Martin, 1996;O'Leary et al, 2002;Medina et al, 2007). It is also demonstrated that object recognition memory was impaired by both endogenous cannabinoid D 9 -THC and synthetic CB 1 receptor agonist WIN 55,212-2 (Schneider and Koch, 2002;Quinn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the activation of the brain cannabinoid system causes deficits in attention, executive functioning, and short-term memory (Lichtman and Martin, 1996;O'Leary et al, 2002;Medina et al, 2007). It is also demonstrated that object recognition memory was impaired by both endogenous cannabinoid D 9 -THC and synthetic CB 1 receptor agonist WIN 55,212-2 (Schneider and Koch, 2002;Quinn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis usage causes deficits in attention, executive functioning, and short-term memory (O'Leary et al, 2002;Medina et al, 2007). We showed earlier that repeated treatment with D 9 -tetrahydrocannabinol (D 9 -THC), the main psychoactive ingredient of marijuana (cannabis), impaired delayed matching-to-sample performance even 24 h after the administration (Miyamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, teenagers who frequently smoke marijuana suffer dysfunctions in synaptic pruning processes and display worse performance in learning tests, cognitive flexibility, visual scanning, error commission and working memory (Medina et al , 2007a, 2007b; Nagel et al , 2005). Sometimes, the sum of these mostly cognitive changes is named ‘Amotivational Syndrome’, and it can be the result of chronic THC intoxication or long lasting effects of the abuse of THC for longer periods of time, with unknown pathophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this seminal paper, the authors demonstrated a dramatic drop in intelligence for those with persistent cannabis dependence. Although Meier et al's study has been the largest and most complete longitudinal examination of IQ decline and marijuana use, there is disagreement as to whether this decline is a direct consequence of marijuana involvement or perhaps attributable to confounding variables (19,24).Although studies have demonstrated that heavy marijuana use may impact IQ test performance even a month after cessation (16,25), deficits seem to be more related to recent use rather than reflecting a permanent insult to cognition (22,26,27). Indeed, some studies find no long-term association of marijuana use and IQ (22,28) or, if so, only on measures of verbal ability (19).…”
mentioning
confidence: 99%
“…There is evidence to suggest that the adolescent brain may be particularly vulnerable, especially with regard to neurocognitive functioning (10,11). Marijuana use in adolescence, when the brain is still undergoing major developmental changes, has been associated with decreased intelligence (12,13), reduced memory (13)(14)(15), poorer attention (16)(17)(18), and lower verbal ability (19)(20)(21). However, these findings come from cross-sectional studies, where the temporal ordering of cause and effect is uncertain.…”
mentioning
confidence: 99%